2006
DOI: 10.1590/s0100-40422006000300011
|View full text |Cite
|
Sign up to set email alerts
|

Caracterização química do "pitch" em indústria de celulose e papel de Eucalyptus

Abstract: Recebido em 23/2/05; aceito em 11/8/05; publicado na web em 8/2/06 CHEMICAL CHARACTERIZATION OF PITCH IN Eucalyptus PULP AND PAPER INDUSTRY. The chemical analysis of the acetone, chloroform, toluene and methanol extracts of a pitch sample was carried out by IR and GC-MS, leading to the identification of sixty nine compounds, including fatty acids, alcohols and hydrocarbons. Analysis of the acetone extractive of a eucalyptus wood used in Brazil for pulp production was also carried out, resulting in identificati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0
6

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 16 publications
(24 reference statements)
2
15
0
6
Order By: Relevance
“…We expected this result because etanol:toluene has greater strength of extraction than water, because organic solvents naturally dissolve some substances that are insoluble in water (fats, fatty acids, sterols, steroids and long-chain alcohols), besides dissolving substances that are water soluble (phenolic compounds, glycosides, sugars, starch, proteins and inorganic salts) (Cruz et al 2006, Esteves et al 2008, Holmbom 1999, Silvério 2008, Sjöström 1993). …”
Section: Soluble Extractives Contentmentioning
confidence: 97%
See 1 more Smart Citation
“…We expected this result because etanol:toluene has greater strength of extraction than water, because organic solvents naturally dissolve some substances that are insoluble in water (fats, fatty acids, sterols, steroids and long-chain alcohols), besides dissolving substances that are water soluble (phenolic compounds, glycosides, sugars, starch, proteins and inorganic salts) (Cruz et al 2006, Esteves et al 2008, Holmbom 1999, Silvério 2008, Sjöström 1993). …”
Section: Soluble Extractives Contentmentioning
confidence: 97%
“…Other authors have reported that Eucalyptus grandis wood naturally has more compounds which are soluble in organic solvents, such as steroids, fatty acids, esters and long-chain alcohols (Barbosa et al 2005, Cruz et al 2006, Silvério 2008.…”
Section: Soluble Extractives Contentmentioning
confidence: 99%
“…[126][127][128][129] Muitas pesquisas sobre a lignina têm sido realizadas para identificar a estrutura de derivados guaiacil (G) e siringil (S), visando determinar o valor da relação S/G deste tipo de macromolécula. [130][131][132][133][134][135][136][137] A aplicação dessa técnica tem demonstrado que a pirólise analítica é ferramenta muito eficaz na avaliação da qualidade da madeira destinada à polpação.…”
Section: Análise De Produtos Da Madeiraunclassified
“…40,127,133,134 Del Río et al 142 aplicaram a Pi-CG-EM para analisar amostras de pitch e de pintas de polímeros sintéticos presentes em diferentes polpas celulósicas. No pirograma obtido foi identificado um sinal referente ao fragmento de polímero sintético.…”
Section: Análise De Produtos Da Madeiraunclassified
“…São constituídos de materiais orgânicos, tais como óleos, gorduras, taninos, carboidratos, ácidos, gomas, graxas e resinas. São produzidos durante o processo de formação do cerne e seus efeitos predominantes estão relacionados à redução da higroscopicidade e permeabilidade da madeira (CRUZ et al, 2006 -FPL, 2010). Os extrativos podem ser volatilizados na prensagem a quente, em função da alta pressão, calor e umidade e pode provocar "bolhas" reduzindo a resistência da ligação interna (MOSLEMI, 1974;MARRA, 1992).…”
Section: Fatores Inerentes a Madeiraunclassified